Evidence for increased efficiency of virus transmission by populations of Mediterranean species of Bemisia tabaci with high Hamiltonella prevalence - Bello, Vinicius Henrique [UNESP] (2019)
Bemisia tabaci is an important agriculture pests and vector of viruses. The MEAM1 species of B. tabaci, first described in Brazil in the 90s is now the most prevalent species and primary cause of the emergence of begomoviruses in tomatoes. The Mediterranean species (MED) was recently detected in Brazil and is a new concern for Brazilian agriculture. The potential impact of this species as a vector of economically important virus in Brazil is unknown. We therefore evaluated the ability of MED to transmit four whitefly transmitted viruses prevalent in Brazil, Cowpea mild mottle virus (CpMMV, carlavirus), Bean golden mosaic virus (BGMV, begomovirus) infecting beans; and the Tomato severe rugose virus (ToSRV, begomovirus), Tomato chlorosis virus (ToCV, crinivirus) infecting tomatoes. The colony of MED harbouring the secondary endosymbionts was tested: 14% positive for Hamiltonella and 29% positive for Rickettsia. After six months being maintained on cotton plants, this colony changed the frequency of endosymbionts (97% of Hamiltonella and 1% of Rickettsia) and was denominated as MEDH. Additionally, a colony of MEAM1 (98% positive for Hamiltonella and 91% positive for Rickettsia) was also tested. The viruses were efficiently transmitted by MED, but transmission efficiency varied among the MED and MEDH, being CpMMV, BGMV and ToCV better transmitted by MEDH. Moreover, transmission efficiency of ToSRV and ToCV by MEDH was even significantly better than MEAM1. We conclude that specimens from B. tabaci MED are good vectors of virus infecting tomato and beans in Brazil and populations with Hamiltonella prevalence increased the virus transmission.